1926
DOI: 10.1084/jem.44.5.667
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Agglutination

Abstract: From the foregoing evidence, specific bacterial agglutination may be conceived of as follows: When bacteria are mixed with their homologous agglutinative sera, specific union between organism and agglutinin occurs. This interaction consists of specific coating of the bacteria by globulin. By virtue of the fact, noted by Loeb and illustrated in Fig. 6, that protein film formation gives the coated particle the characteristics of denatured protein, the bacteria now take on the character of particles of denatured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1929
1929
1955
1955

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…The Action of Immune Sera.--Shibley (33) has shown that bacteria treated with immune sera have electrophoretic velocities practically equal to that of serum globulin particles. The reaction of the bacteria with specific groups belonging to serum globulin can occur without disturbing the amphoteric properties of the globulin as the simpler models here studied indicate.…”
Section: R-phycoerythrin and C-phycocyanmentioning
confidence: 99%
“…The Action of Immune Sera.--Shibley (33) has shown that bacteria treated with immune sera have electrophoretic velocities practically equal to that of serum globulin particles. The reaction of the bacteria with specific groups belonging to serum globulin can occur without disturbing the amphoteric properties of the globulin as the simpler models here studied indicate.…”
Section: R-phycoerythrin and C-phycocyanmentioning
confidence: 99%
“…In this work (8) it has been shown that sensitization of bacteria by agglutinative sera is selective coating by antibody globulin, that by such film formation at their surface, the bacteria take on the characteristics of particles of denatured globulin and that subsequent agglutination of the coated bacteria follows the laws governing the flocculation of particles of denatured protein by electrolytes. For effective selective coating of bacteria by agglutinin it would seem essential that the antibody be intact.…”
Section: Discussionmentioning
confidence: 99%
“…The agglutinin has the power t o bring about the death of the protozoon although the action is not very rapid. The conception of the action of an agglutinin as primarily a coating of the surface or part of the surface of the cell by the homologous element in the serum, put forward by Bordet (1899) and Arkwright (1931) and restated in the light of more modern work by Shibley (1926)) is generally accepted.…”
Section: Discussionmentioning
confidence: 99%